2003
DOI: 10.1292/jvms.65.1037
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of Ateliosis in Japanese Black Calves and their Secretory Function of Growth Hormone

Abstract: ABSTRACT. Unthrifty calves occurred sporadically in Japanese Black (beef cattle) in an area in northeastern Japan. The states of unthrifty development, pedigree, clinico-biochemistry and the secretory function of bovine growth hormone (bGH) in pituitary were investigated. The total cholesterol concentration and CK, AST and LDH activities in the serum showed higher values than those of control calves. Basal bGH concentrations in the serum and bGH secretory reactivity in the insulin tolerance test (ITT) were sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
8
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 4 publications
1
8
0
Order By: Relevance
“…Thus, strain-specific endocrine and metabolic features should be considered as well as their meat characteristics. Some researchers have considered growth retardation in Japanese black cattle to be intimately related to pedigree and to be hereditary [9,14,15]. Our data above might support their conclusions.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Thus, strain-specific endocrine and metabolic features should be considered as well as their meat characteristics. Some researchers have considered growth retardation in Japanese black cattle to be intimately related to pedigree and to be hereditary [9,14,15]. Our data above might support their conclusions.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, some researchers have considered familial hypothyroidism to be a primary cause of growth retardation [14,15]. Moreover, it was previously reported that hypothyroidism in Japanese black cattle with growth retardation in the central Japan region showed euthyroid sick syndrome caused by malnutrition and astasia [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested that neonatal weak calf syndrome is associated with asiderotic anemia and immunodeficiency [16], and that hypogenesis syndrome is associated with growth hormone (GH) deficiency [17], insulin like growth factor-1 (IGF-1) deficiency in contrast with hypersecretion of GH [5,6,11,26], primary or secondary underactive thyroid function [5,6,24,30] and other factors.…”
mentioning
confidence: 99%
“…To reduce such losses, researchers have attempted to determine the cause of the growth retardation [5,6]. However, nutriture of the cattle with growth retardation has yet to be clarified.…”
mentioning
confidence: 99%